2021
DOI: 10.1177/03000605211049653
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum S100A10 in lung cancer

Abstract: Objective To investigate the clinical significance of serum S100 calcium-binding protein A10 (S100A10) levels in lung cancer. Methods This prospective study enrolled patients with lung cancer, patients with benign lung nodules and healthy control subjects. Serum S100A10 levels and three biomarkers were measured and compared between the groups. Associations between serum S100A10 and clinical characteristics in patients with lung cancer were investigated. The diagnostic efficacy of serum S100A10 and carcinoembry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…In lung squamous cell carcinoma, the expression of S100A10 in tumor tissue was positively correlated with tumor size, TMN stage, and lymphatic metastasis [8], while elevated S100A10 in lung adenocarcinoma indicated poorer tumor differentiation, higher TMN stage, more frequent intratumoral vascular invasion and a poorer prognosis [17]. What is more, the serum S100A10 levels in lung cancer were not only significantly higher than that in patients with benign lung nodules and healthy cancer-free controls but also positively associated with TNM stage and lymphatic metastasis [18], indicating that S100A10 is not only a prognostic marker but also a potential diagnostic maker for lung cancer. Similarly, Yi Tan et al reported that S100A10 might serve as a potential biomarker for early detection and a potential therapeutic target for gallbladder cancer [9].…”
Section: Discussionmentioning
confidence: 97%
“…In lung squamous cell carcinoma, the expression of S100A10 in tumor tissue was positively correlated with tumor size, TMN stage, and lymphatic metastasis [8], while elevated S100A10 in lung adenocarcinoma indicated poorer tumor differentiation, higher TMN stage, more frequent intratumoral vascular invasion and a poorer prognosis [17]. What is more, the serum S100A10 levels in lung cancer were not only significantly higher than that in patients with benign lung nodules and healthy cancer-free controls but also positively associated with TNM stage and lymphatic metastasis [18], indicating that S100A10 is not only a prognostic marker but also a potential diagnostic maker for lung cancer. Similarly, Yi Tan et al reported that S100A10 might serve as a potential biomarker for early detection and a potential therapeutic target for gallbladder cancer [9].…”
Section: Discussionmentioning
confidence: 97%
“…This, in turn, can cause matrix metalloproteinase activation, extracellular matrix degradation, and the consequent growth and invasivity of tumors [8]. Aberrant S100A10 upregulation has been reported in lung, gastric, ovarian, and breast cancers wherein it is associated with poorer prognostic outcomes [9][10][11][12]. To date, there have been no detailed analyses of S100A10 expression in cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC), and further work is vital to clarify its biological activity in this deadly oncogenic context.…”
Section: Ivyspring International Publishermentioning
confidence: 99%